Dairy herd profitability: effects of milk yield and cost of production on net returns - Delano, F.D.; Langemeier, Michael R. (Kansas Agricultural Experiment Station, 2011)
Dairy cow herd enterprise records from Kansas Farm Management Association farms over the past 4 years have shown an increase in returns to labor and management from $252 to $355 per cow. Returns for higher milkproducing cows were over $400 each. Cost per hundred weight of milk produced per cow for the higher-producing herds compared with lower-producing herds was about the same. In 1994, for every extra $1.00 spent on feed and other variable costs, the higher-producing herds earned $1.28.
Typo of author's name L. N. Langemeier; should be M. R. Langemeier.
Keywords: Profitability; Production costs; Production returns